Understanding the meaning of lafz sarra, arada and ahabba in the hadith about friendship in the sahihayn - Bahrul Jadid (Penerbit Universiti Kebangsaan Malaysia, 2024)
Each Arabic lafz carries distinct nuances of meaning, yet their variations and deeper implications for understanding the concept of friendship (kinship and social bonds) in Islam remain underexplored, particularly in the context of hadiths from Sahih Bukhari and Sahih Muslim. This study aims to analyze the meaning of the lafz sarra (ر سَ), arada (َرادََأ), and ahabba (ب حََأ) as found in five hadiths related to friendship from the books of Sahih Bukhari and Sahih Muslim. The research addresses the problem of how variations in lafz contribute to a deeper understanding of the multidimensional nature of friendship, encompassing emotional, intentional, and relational aspects.To achieve this, the study employs linguistic, contextual, and thematic methods. The linguistic analysis involves examining the etymology and semantic evolution of the selected lafz. Contextual analysis focuses on the situational background and circumstances under which the hadiths were conveyed. Thematic analysis synthesizes the meanings derived from these lafz to uncover their broader implications for the concept of friendship in Islamic teachings.The findings reveal that each lafz represents a distinct dimension of friendship: sarra reflects the happiness or satisfaction derived from fostering positive relationships, arada conveys a strong will or desire to maintain bonds, and ahabba emphasizes the element of love and affection within social connections. This comprehensive analysis demonstrates how friendship, as emphasized by the Prophet Muhammad, brings blessings, strengthens social relationships, and increases the blessings of sustenance and longevity.